High Gain Slot Array Antenna at 110 GHz Based on Computer Numerical Control - Zhen Tan; Yun Zhao; Jiangqiao Ding (Micromachines, 2023)
This paper presents a waveguide–slot antenna to generate a radiation beam with high gain fed by a low-loss feeding network at 110 GHz. The proposed antenna consists of a compact eight-way power divider and a waveguide–slot array. The eight-way power divider provides equal-amplitude and alternative-phase excitation for the slot array, and each of them supports two waveguides. The integral structure is implemented by two layers with a channeled substratum and a slotted superstratum. To verify the proposed slot array, the designed array is fabricated with computer numerical control (CNC) milling and measured. The measured peak gain of the designed antenna is 32 dBi at 110 GHz. The proposed antenna with a simple structure provides a promising solution to develop high gain antenna in upper millimeter-wave and sub-terahertz (THz) applications.